Innovative Potential of Regional Economic Systems under Conditions of Variability of Ecological and Economic Processes - АKZHANOVA, Gulzira; BAKIRBEKOVA, Aigul; DEMESSINOV, Talgat; SHMARLOUSKAYA, Halina; SMAGULOVA, Zubirash (Journal of Environmental Management and Tourism; Vol 13 No 7 (2022): JEMT, Volume XIII, Issue 7(63), Winter 2022, 2022)
In this paper, the authors studied the theoretical basis for the formation of the innovative potential for the development of ecological and economic regional systems, analyzed the indicators characterizing the level of innovative development of regions, developed recommendations for improving the innovative potential of ecological and economic regional systems. The influence of external factors, including the global pandemic, on regional economic systems requires an adequate identification of the dependence of the process of forming innovative potential on the degree of their development. In this regard, the difference in socio-economic conditions for the development of regions, as well as cardinal changes in scientific paradigms and theories, require a reasoned justification of the principles of the concept of forming the innovative potential of economic regional systems in the context of the rapidity of technological patterns and ecological influences. All this reinforces the need to substantiate the theoretical and methodological key concepts of development and formation of the innovative potential of economic systems of regions, determined by an understanding of the economic essence of the category “innovation potential” adapted to modern conditions of economic development, considering the factor dependence of the formation of stable and dynamic development of economic mesosystems.